The impact of media use on disparities in physical and mental health among the older people: An empirical analysis from China - Wang, Han; Sun, Xiaojun; Wang, Ruyue; Yang, Yang; Wang, Yuwei (Frontiers in Public Health, 2022)
Objectives: The purpose of this study was to investigate the media use, physical and mental health (Self-rated health and subjective well-being) levels of older adults in China, the relationship between different media types use (Traditional media, internet media), and physical and mental health levels and the effects of different media types use on physical and mental health disparities among older adults with varying levels of education. Methods: The data used in this study are from the China General Social Survey. The descriptive statistical analysis was conducted on the media use and the health levels of Chinese older adults; analysis of variance and post hoc analysis were used to analyze the differences in health levels and frequency of media use among older people with different levels of education; bivariate correlation and regression analyses were conducted to explore the relationship between media use and health levels in older adults; multilevel regression analyses and simple slope plots explored whether the use of different media types widened or narrowed the gap in health levels among older people with varying levels of education. Results: The results of the study show that (1) the self-rated health levels are lower in the old people group relative to subjective well-being. While some older adults have mastered the internet media, most of the older population is more accustomed to using traditional media (Especially TV, 77.08% of the elderly are used to watching TV regularly). There are disparities in media use habits and health levels among older adults with different education levels. (2) traditional media use was a significant positive predictor of physical and mental health in the older age group. internet media use was a significant positive predictor of physical health in the older age group. (3) traditional and internet media use could narrow the physical and mental health disparities between older people with different education levels. Conclusions:Society should value the media's important role in promoting older persons' health and well-being. Government-related departments can combine the media with public health campaigns to narrow the health disparity among old people with different educational levels and promote equal healthy aging.